Komposisi dan Struktur Komunitas Karang (Scleractinia) di Ekosistem Terumbu Karang di Perairan Pantai Nirwana Padang - Vany Helsa Anwar; Indra Junaidi Zakaria; Afrizal S (Universitas Andalas, 2014)
A study on the composition and community structure of Scleractinia in coral reef ecosystem at coastal region Taman Nirwana Padang have been done from April - July 2013. This study was to know the competition and community structure of Scleractinia at coastal region Taman Nirwana Padang. The research was conducted by